Radioactivity Levels in Water Samples of Tigris River in Baghdad City, Iraq - Mohammed, Akram A.; Tawfiq, Nada F. (Iraqi Journal of Science, 2022)
The natural radioactivity levels in water samples along the Tigris river (one of the major rivers of the world) within Baghdad city were investigated to determine and evaluate the radioactivity risks in the water of the river. The specific activity of the radionuclides (238U, 232Th, 40K, and 137Cs) for thirty different water samples from Tigris river within Baghdad city were measured using gamma-ray spectrometer, employing a NaI(Tl) scintillation detector. The results showed that the average value of the specific activity for 238U, 232Th, 40K, and 137Cs were (24.20, 16.70, 329.22, and 19.40) Bq/l, respectively. The calculated average annual effective doses for different age groups were found to be (3.80, 6.57, and 5.59) mSv/y for infants, children, and adults, respectively, which are much higher than the globally allowed annual limits of the dose (0.26, 0.2 and 0.1) mSv/y  for infants, children and adults, respectively, and it has harmful effects on health.